High-voltage-resistant polysilazane-based insulating material for power battery pack of new energy automobile and preparation method of high-voltage-resistant polysilazane-based insulating material

By introducing silicon carbide microspheres, carbon nitride modified metal organic supramolecular cages and lanthanum modified carbon nanotubes into polysilica nitride-molecular cages, the problem of insufficient withstand voltage and mechanical strength of the material in high temperature and high voltage environments is solved, and the development of high-performance insulating materials is achieved.

CN120209586AActive Publication Date: 2025-06-27JIANGXI YANXUN SILICON MATERIALS CO LTD

Patent Information

Application Number
CN202510369742.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-27
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing polysilica niac insulating materials have insufficient voltage resistance and mechanical strength in high temperature and high voltage environments, which cannot meet the safety and reliability requirements of new energy vehicle power battery packs.

Method used

Silicon carbide microspheres are prepared by reacting polycarbosilane with polyaniline, and hydrothermal deposition and organic boron coating of molybdenum disulfide to improve thermal conductivity, electrical insulation and flame retardant properties; at the same time, through carbon nitride modification and surface modification, the thermal conductivity, interface binding and dielectric properties of metal organic supramolecular cages are improved; finally, through acid treatment of carbon nanotubes, rare earth lanthanum modification and boron nitride composite, their dispersion, thermal conductivity and insulating properties are improved.

Benefits of technology

It achieves high voltage withstand voltage, excellent thermal performance, electrical performance and mechanical performance, and meets the high-performance insulation material needs of new energy vehicle power battery packs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120209586A_ABST
    Figure CN120209586A_ABST
Patent Text Reader

Abstract

The invention provides a high-voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy automobile and a preparation method of the high-voltage-resistant polysilazane-based insulating material, and belongs to the technical field of insulating materials. The silicon carbide microspheres are prepared through reaction of polycarbosilane and polyaniline, and through hydrothermal deposition of molybdenum disulfide and coating of organic boron, the heat-conducting property, the electrical insulating property and the flame retardant property of the silicon carbide microspheres are improved; secondly, the prepared metal organic supramolecular cage is subjected to carbon nitride modification and surface modification, so that the thermal conductivity, the interface bonding force and the dielectric property of the metal organic supramolecular cage are improved; in addition, the carbon nanotubes are subjected to acid treatment, rare earth lanthanum modification and boron nitride compounding, so that the dispersity, the thermal conductivity and the insulating property of the carbon nanotubes are remarkably improved; through the synergistic effect of all the components, the thermal performance, the electrical performance and the mechanical performance of the composite material are comprehensively optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of insulating materials and relates to a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack and a preparation method thereof. Background Art

[0002] In the current global energy transformation context, new energy vehicles, as an important solution to promote sustainable development and reduce carbon emissions, are ushering in opportunities for rapid development. With the rapid growth of the electric vehicle market, the performance and safety of power battery packs, as the core components of new energy vehicles, have become the focus of industry attention. Power battery packs not only carry the functions of storing and releasing electrical energy, but also need to maintain a stable working state under different working conditions. Therefore, choosing the right insulating material to ensure the safety, durability and energy conversion efficiency of the battery is the key to improving the overall performance of new energy vehicles.

[0003] Insulating materials play a vital role in power battery packs. They not only need to have excellent electrical insulation properties to prevent current leakage and short circuits, but also need to have good mechanical strength to withstand the stress caused by extreme environments such as high voltage and high temperature. At the same time, insulating materials must also be corrosion-resistant to cope with the chemical reactions that may occur during the charging and discharging process of the battery. Polysilazane-based materials have gradually attracted the attention of researchers due to their excellent thermal stability, electrical insulation and chemical tolerance. This material not only has good thermal stability and can maintain stable performance at high temperatures, but also exhibits excellent electrical insulation properties and is suitable for high-voltage environments.

[0004] However, despite the significant advantages of polysilazane-based materials, existing polysilazane-based insulating materials still have deficiencies in voltage resistance and mechanical strength, especially in terms of stability and insulation performance maintenance under high temperature and high voltage environments. This makes traditional polysilazane-based materials unable to meet safety and reliability standards in certain high-demand application scenarios, such as future electric vehicle fast charging technology and high-voltage environments required by high-power battery systems. Therefore, there is an urgent need to develop new high-performance polysilazane-based insulating materials to meet these challenges, thereby providing more reliable protection for the safety and durability of new energy vehicles. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs and a preparation method thereof. The present invention prepares silicon carbide microspheres by reacting polycarbosilane with polyaniline, and improves its thermal conductivity, electrical insulation and flame retardancy through hydrothermal deposition of molybdenum disulfide and organic boron coating; secondly, the prepared metal-organic supramolecular cage is modified by carbon nitride and surface modification, improving its thermal conductivity, interfacial bonding force and dielectric properties; in addition, carbon nanotubes are acid-treated, rare earth lanthanum-modified and boron nitride composite, significantly improving its dispersibility, thermal conductivity and insulation properties. The synergistic effect among the components comprehensively optimizes the thermal, electrical and mechanical properties of the composite material, providing important support for the development of high-performance insulating materials.

[0006] To achieve this purpose, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a preparation method of a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs, and the preparation method of the high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs includes:

[0008] S11: Mix polycarbosilane and polyaniline, react at a constant temperature in an inert atmosphere, cool and filter to obtain a first product, soak it in a mixed acid solution, centrifuge, wash and dry to obtain silicon carbide microspheres;

[0009] S12: Disperse the silicon carbide microspheres in deionized water, add ammonium heptamolybdate and sodium sulfide after ultrasonic dispersion and carry out hydrothermal reaction, centrifuge, wash and dry to obtain silicon carbide / molybdenum disulfide composite materials;

[0010] S13: Dissolve boron trifluoride diethyl ether complex and phenyltrimethoxysilane in tetrahydrofuran and stir to obtain a modified solution, add the silicon carbide / molybdenum disulfide composite material to obtain reaction solution A, stir at a constant temperature and cure to obtain an organic boron-coated silicon carbide / molybdenum disulfide composite material;

[0011] S21: Dissolve trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water, carry out solvothermal reaction, filter and wash to obtain a metal-organic supramolecular cage;

[0012] S22: Calcinate melamine to obtain carbon nitride, add it to concentrated nitric acid and carry out reflux reaction, filter, wash and dry to obtain modified carbon nitride, disperse the modified carbon nitride and the metal-organic supramolecular cage in N,N-dimethylformamide and mix evenly, then carry out solvothermal reaction, filter, wash and dry to obtain carbon nitride-modified metal-organic supramolecular cages;

[0013] S23: Disperse the carbon nitride modified metal-organic supramolecular cage in anhydrous toluene, add 3-trifluoropropyltriethoxysilane, carry out reflux reaction, and obtain a pretreated product after centrifugation, washing, and drying, and obtain a composite modified metal-organic supramolecular cage through vacuum curing;

[0014] S31: Stir and modify the carbon nanotubes in the modified acid solution to obtain modified carbon nanotubes. Disperse the modified carbon nanotubes in a lanthanum nitrate solution, add sodium hydroxide to adjust the pH to obtain reaction solution B, carry out heat treatment under an argon atmosphere, and obtain lanthanum-modified carbon nanotubes after filtration, washing, and drying;

[0015] S32: Ultrasonically exfoliate hexagonal boron nitride in N-methylpyrrolidone, centrifuge and collect the supernatant for standby. Disperse the lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion liquid, mix it with the supernatant and carry out a reaction, then carry out vacuum filtration, pre-drying, and heat treatment to obtain boron nitride / lanthanum-modified carbon nanotubes;

[0016] S33: Disperse the boron nitride / lanthanum-modified carbon nanotubes in absolute ethanol, add 3-aminopropyltriethoxysilane and triethylamine, mix evenly and carry out a constant-temperature reaction, and obtain a composite modified lanthanum-modified carbon nanotube after filtration, washing, and pre-drying and then curing;

[0017] A1: Disperse polysilazane in anhydrous toluene. After dispersing evenly, successively add an organoboron-coated silicon carbide / molybdenum disulfide composite material, a composite modified metal-organic supramolecular cage, a composite modified lanthanum-modified carbon nanotube, a crosslinking agent, and a flame retardant, stir to obtain a mixed liquid, pour it into a mold, carry out defoaming, pre-curing, heat curing under an inert atmosphere, and then naturally cool to obtain a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs.

[0018] As a preferred technical solution of the present invention, in S11, the mass ratio of the polycarbosilane to the polyaniline is 1:(1 - 1.2), for example, it can be 1:1.00, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.10, 1:1.12, 1:1.14, 1:1.16, 1:1.18, or 1:1.20, but it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0019] In some alternative embodiments, the temperature of the constant-temperature reaction under the inert atmosphere is 1400 - 1500 °C, for example, it can be 1400 °C, 1410 °C, 1420 °C, 1430 °C, 1440 °C, 1450 °C, 1460 °C, 1470 °C, 1480 °C, 1490 °C, or 1500 °C, but it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0020] In some alternative embodiments, the time for the constant-temperature reaction under an inert atmosphere is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0021] In some alternative embodiments, the volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is (2 - 3):1. For example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, or 3.0:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0022] In some alternative embodiments, the mass ratio of the first product to the mixed acid solution is 1:(20 - 30). For example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29, or 1:30. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0023] In some alternative embodiments, the soaking time of the first product in the mixed acid solution is 4 - 6 h. For example, it can be 4.0 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5.0 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, or 6.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0024] As a preferred technical solution of the present invention, in S12, the mass fraction of the silicon carbide microspheres in deionized water is 0.8 - 1.2 wt.%. For example, it can be 0.80%, 0.84%, 0.88%, 0.92%, 0.96%, 1.00%, 1.04%, 1.08%, 1.12%, 1.16%, or 1.20%. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0025] In some alternative embodiments, the molar ratio of ammonium heptamolybdate to sodium sulfide is 1:(2 - 3). For example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, or 1:3.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0026] In some alternative embodiments, the mass ratio of silicon carbide to ammonium heptamolybdate is 1:(0.2 - 0.3), for example, it can be 1:0.20, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29 or 1:0.30. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0027] In some alternative embodiments, the temperature of the hydrothermal reaction is 170 - 180 °C, for example, it can be 170 °C, 171 °C, 172 °C, 173 °C, 174 °C, 175 °C, 176 °C, 177 °C, 178 °C, 179 °C or 180 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0028] In some alternative embodiments, the time of the hydrothermal reaction is 10 - 14 h, for example, it can be 10.0 h, 10.4 h, 10.8 h, 11.2 h, 11.6 h, 12.0 h, 12.4 h, 12.8 h, 13.2 h, 13.6 h or 14.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0029] As a preferred technical solution of the present invention, in S13, the molar ratio of boron trifluoride ether complex to phenyltrimethoxysilane is (0.8 - 1.2):1, for example, it can be 0.80:1, 0.84:1, 0.88:1, 0.92:1, 0.96:1, 1.00:1, 1.04:1, 1.08:1, 1.12:1, 1.16:1 or 1.20:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0030] In some alternative embodiments, the total mass fraction of boron trifluoride ether complex and phenyltrimethoxysilane in the modification solution is 5 - 8 wt.%, for example, it can be 5.0%, 5.3%, 5.6%, 5.9%, 6.2%, 6.5%, 6.8%, 7.1%, 7.4%, 7.7% or 8.0%. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0031] In some alternative embodiments, the solid-liquid mass ratio of the silicon carbide / molybdenum disulfide composite material to the modification solution is 1:(15 - 25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or 1:25. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0032] In some alternative embodiments, the temperature for constant temperature stirring of the reaction solution A is 60 - 70 °C. For example, it can be 60 °C, 61 °C, 62 °C, 63 °C, 64 °C, 65 °C, 66 °C, 67 °C, 68 °C, 69 °C or 70 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0033] In some alternative embodiments, the time for constant temperature stirring of the reaction solution A is 5 - 7 h. For example, it can be 5.0 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, 6.0 h, 6.2 h, 6.4 h, 6.6 h, 6.8 h or 7.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0034] In some alternative embodiments, the curing temperature is 250 - 280 °C. For example, it can be 250 °C, 253 °C, 256 °C, 259 °C, 262 °C, 265 °C, 268 °C, 271 °C, 274 °C, 277 °C or 280 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0035] In some alternative embodiments, the curing time is 1.5 - 2.5 h. For example, it can be 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h or 2.5 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0036] As a preferred technical solution of the present invention, in S21, the molar ratio of trimesic acid to zinc nitrate hexahydrate is 1:(1 - 2). For example, it can be 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0037] In some alternative embodiments, the volume ratio of N,N - dimethylformamide to deionized water in the mixed solvent is (4 - 5):1. For example, it can be 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5.0:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0038] In some alternative embodiments, the total concentration of trimellitic acid and zinc nitrate hexahydrate in the mixed solvent is 0.05 - 0.1 M. For example, it can be 0.050 M, 0.055 M, 0.060 M, 0.065 M, 0.070 M, 0.075 M, 0.080 M, 0.085 M, 0.090 M, 0.095 M, or 0.100 M. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0039] In some alternative embodiments, the temperature of the solvothermal reaction is 110 - 130 °C. For example, it can be 110 °C, 112 °C, 114 °C, 116 °C, 118 °C, 120 °C, 122 °C, 124 °C, 126 °C, 128 °C, or 130 °C. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0040] In some alternative embodiments, the time of the solvothermal reaction is 45 - 50 h. For example, it can be 45.0 h, 45.5 h, 46.0 h, 46.5 h, 47.0 h, 47.5 h, 48.0 h, 48.5 h, 49.0 h, 49.5 h, or 50.0 h. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0041] As a preferred technical solution of the present invention, in S22, the temperature for calcining melamine is 530 - 580 °C. For example, it can be 530 °C, 535 °C, 540 °C, 545 °C, 550 °C, 555 °C, 560 °C, 565 °C, 570 °C, 575 °C, or 580 °C. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0042] In some alternative embodiments, the time for calcining melamine is 3 - 5 h. For example, it can be 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4.0 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, or 5.0 h. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0043] In some alternative embodiments, the mass fraction of carbon nitride in concentrated nitric acid is 2 - 5 wt.%. For example, it can be 2.0%, 2.3%, 2.6%, 2.9%, 3.2%, 3.5%, 3.8%, 4.1%, 4.4%, 4.7%, or 5.0%. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0044] In some alternative embodiments, the temperature of the reflux reaction is 120 - 130 °C, for example, it can be 120 °C, 121 °C, 122 °C, 123 °C, 124 °C, 125 °C, 126 °C, 127 °C, 128 °C, 129 °C or 130 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0045] In some alternative embodiments, the time of the reflux reaction is 7 - 9 h, for example, it can be 7.0 h, 7.2 h, 7.4 h, 7.6 h, 7.8 h, 8.0 h, 8.2 h, 8.4 h, 8.6 h, 8.8 h or 9.0 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0046] In some alternative embodiments, the mass ratio of the modified carbon nitride to the metal - organic supramolecular cage is (0.8 - 1.2):1, for example, it can be 0.80:1, 0.84:1, 0.88:1, 0.92:1, 0.96:1, 1.00:1, 1.04:1, 1.08:1, 1.12:1, 1.16:1 or 1.20:1, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0047] In some alternative embodiments, the mass fraction of the modified carbon nitride in N,N - dimethylformamide is 1 - 2 wt.%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0048] In some alternative embodiments, the temperature of the solvothermal reaction is 130 - 150 °C, for example, it can be 130 °C, 132 °C, 134 °C, 136 °C, 138 °C, 140 °C, 142 °C, 144 °C, 146 °C, 148 °C or 150 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0049] In some alternative embodiments, the time of the solvothermal reaction is 10 - 14 h, for example, it can be 10.0 h, 10.4 h, 10.8 h, 11.2 h, 11.6 h, 12.0 h, 12.4 h, 12.8 h, 13.2 h, 13.6 h or 14.0 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0050] As a preferred technical solution of the present invention, in S23, the mass fraction of the carbon nitride modified metal-organic supramolecular cage in anhydrous toluene is 1-2 wt.%, for example, it can be 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.% or 2.0 wt.%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0051] In some alternative embodiments, the feeding amount of the trifluoropropyltriethoxysilane accounts for 4-6% of the mass of the carbon nitride modified metal-organic supramolecular cage, for example, it can be 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8% or 6.0%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0052] In some alternative embodiments, the temperature of the reflux reaction is 115-125 °C, for example, it can be 115 °C, 116 °C, 117 °C, 118 °C, 119 °C, 120 °C, 121 °C, 122 °C, 123 °C, 124 °C or 125 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0053] In some alternative embodiments, the time of the reflux reaction is 5-7 h, for example, it can be 5.0 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, 6.0 h, 6.2 h, 6.4 h, 6.6 h, 6.8 h or 7.0 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0054] In some alternative embodiments, the temperature of the vacuum curing is 120-140 °C, for example, it can be 120 °C, 122 °C, 124 °C, 126 °C, 128 °C, 130 °C, 132 °C, 134 °C, 136 °C, 138 °C or 140 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0055] In some alternative embodiments, the time of the vacuum curing is 1.5-2.5 h, for example, it can be 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h or 2.5 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0056] As a preferred technical solution of the present invention, in S31, the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the modified acid solution is (3-4):1. For example, it can be 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1 or 4.0:1. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0057] In some alternative embodiments, the mass ratio of the carbon nanotubes to the modified acid solution is 1:(20-30). For example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0058] In some alternative embodiments, the temperature for stirring and modifying the carbon nanotubes in the modified acid solution is 80-90°C. For example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0059] In some alternative embodiments, the time for stirring and modifying the carbon nanotubes in the modified acid solution is 5-7h. For example, it can be 5.0h, 5.2h, 5.4h, 5.6h, 5.8h, 6.0h, 6.2h, 6.4h, 6.6h, 6.8h or 7.0h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0060] In some alternative embodiments, the concentration of the lanthanum nitrate solution is 0.1-0.2M. For example, it can be 0.10M, 0.11M, 0.12M, 0.13M, 0.14M, 0.15M, 0.16M, 0.17M, 0.18M, 0.19M or 0.20M. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0061] In some alternative embodiments, the mass ratio of the lanthanum nitrate to the modified carbon nanotubes is 1:(8-12). For example, it can be 1:8.0, 1:8.4, 1:8.8, 1:9.2, 1:9.6, 1:10.0, 1:10.4, 1:10.8, 1:11.2, 1:11.6 or 1:12.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0062] In some alternative embodiments, adding sodium hydroxide to adjust the pH to 8 - 9, for example, it can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0063] In some alternative embodiments, the temperature for heat treatment of the reaction solution B in an argon atmosphere is 480 - 520 °C, for example, it can be 480 °C, 484 °C, 488 °C, 492 °C, 496 °C, 500 °C, 504 °C, 508 °C, 512 °C, 516 °C or 520 °C, but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0064] In some alternative embodiments, the heat treatment time of the reaction solution B in an argon atmosphere is 1 - 2 h, for example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0065] As a preferred technical solution of the present invention, in S32, the concentration of hexagonal boron nitride in N - methylpyrrolidone is 0.5 - 1 mg / mL, for example, it can be 0.50 mg / mL, 0.55 mg / mL, 0.60 mg / mL, 0.65 mg / mL, 0.70 mg / mL, 0.75 mg / mL, 0.80 mg / mL, 0.85 mg / mL, 0.90 mg / mL, 0.95 mg / mL or 1.00 mg / mL, but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0066] In some alternative embodiments, the concentration of lanthanum - modified carbon nanotubes in the first dispersion is 1 - 2 mg / mL, for example, it can be 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL or 2.0 mg / mL, but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0067] In some alternative embodiments, the mass ratio of the first dispersion to the supernatant when they are mixed is (1.2 - 1.8):1. For example, it can be 1.20:1, 1.26:1, 1.32:1, 1.38:1, 1.44:1, 1.50:1, 1.56:1, 1.62:1, 1.68:1, 1.74:1, or 1.80:1. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0068] In some alternative embodiments, the time for the mixing reaction is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0069] In some alternative embodiments, the temperature for pre - drying is 70 - 80 °C. For example, it can be 70 °C, 71 °C, 72 °C, 73 °C, 74 °C, 75 °C, 76 °C, 77 °C, 78 °C, 79 °C, or 80 °C. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0070] In some alternative embodiments, the time for pre - drying is 3 - 4 h. For example, it can be 3.0 h, 3.1 h, 3.2 h, 3.3 h, 3.4 h, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h, or 4.0 h. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0071] In some alternative embodiments, the temperature for heat treatment is 280 - 320 °C. For example, it can be 280 °C, 284 °C, 288 °C, 292 °C, 296 °C, 300 °C, 304 °C, 308 °C, 312 °C, 316 °C, or 320 °C. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0072] In some alternative embodiments, the time for heat treatment is 25 - 35 min. For example, it can be 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, or 35 min. However, it is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0073] As a preferred technical solution of the present invention, in S33, the mass fraction of the boron nitride / lanthanum modified carbon nanotubes in absolute ethanol is 2-3 wt.%, for example, it can be 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.%, 2.5 wt.%, 2.6 wt.%, 2.7 wt.%, 2.8 wt.%, 2.9 wt.% or 3.0 wt.%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0074] In some alternative embodiments, the feeding amount of the 3-aminopropyltriethoxysilane accounts for 4-6% of the mass of the boron nitride / lanthanum modified carbon nanotubes, for example, it can be 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8% or 6.0%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0075] In some alternative embodiments, the feeding amount of the triethylamine accounts for 0.5-1% of the mass of the boron nitride / lanthanum modified carbon nanotubes, for example, it can be 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% or 1.00%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0076] In some alternative embodiments, the temperature of the constant temperature reaction is 50-60 °C, for example, it can be 50 °C, 51 °C, 52 °C, 53 °C, 54 °C, 55 °C, 56 °C, 57 °C, 58 °C, 59 °C or 60 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0077] In some alternative embodiments, the time of the constant temperature reaction is 2-3 h, for example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0078] In some alternative embodiments, the temperature of the pre-drying is 70-80 °C, for example, it can be 70 °C, 71 °C, 72 °C, 73 °C, 74 °C, 75 °C, 76 °C, 77 °C, 78 °C, 79 °C or 80 °C, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0079] In some alternative embodiments, the time for pre-drying is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0080] In some alternative embodiments, the temperature for curing is 140 - 150 °C. For example, it can be 140 °C, 141 °C, 142 °C, 143 °C, 144 °C, 145 °C, 146 °C, 147 °C, 148 °C, 149 °C, or 150 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0081] In some alternative embodiments, the time for curing is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0082] As a preferred technical solution of the present invention, in A1, the mass fraction of the polysilazane in anhydrous toluene is 20 - 25 wt.%. For example, it can be 20.0 wt.%, 20.5 wt.%, 21.0 wt.%, 21.5 wt.%, 22.0 wt.%, 22.5 wt.%, 23.0 wt.%, 23.5 wt.%, 24.0 wt.%, 24.5 wt.%, or 25.0 wt.%. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0083] In some alternative embodiments, the temperature for pre-curing is 70 - 80 °C. For example, it can be 70 °C, 71 °C, 72 °C, 73 °C, 74 °C, 75 °C, 76 °C, 77 °C, 78 °C, 79 °C, or 80 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0084] In some alternative embodiments, the time for pre-curing is 3 - 4 h. For example, it can be 3.0 h, 3.1 h, 3.2 h, 3.3 h, 3.4 h, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h, or 4.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0085] In some alternative embodiments, the temperature for thermal curing under an inert atmosphere is 200 - 250 °C. For example, it can be 200 °C, 205 °C, 210 °C, 215 °C, 220 °C, 225 °C, 230 °C, 235 °C, 240 °C, 245 °C or 250 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0086] In some alternative embodiments, the time for thermal curing under an inert atmosphere is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0087] In a second aspect, the present invention provides a high-voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy vehicle. The high-voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy vehicle includes polysilazane, an organoboron-coated silicon carbide / molybdenum disulfide composite material, a composite-modified metal-organic supramolecular cage, a composite-modified lanthanum-modified carbon nanotube, a crosslinking agent, and a flame retardant. The mass ratio of polysilazane, the organoboron-coated silicon carbide / molybdenum disulfide composite material, the composite-modified metal-organic supramolecular cage, the composite-modified lanthanum-modified carbon nanotube, the crosslinking agent, and the flame retardant in the high-voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy vehicle is: (80 - 85):(30 - 40):(35 - 45):(25 - 35):(4 - 5):(3 - 4).

[0088] The crosslinking agent is any one or a combination of two of vinyltrimethoxysilane, vinyltriethoxysilane, or γ-methacryloxypropyltrimethoxysilane;

[0089] The flame retardant is any one or a combination of two of aluminum hydroxide, magnesium hydroxide, or ammonium polyphosphate.

[0090] The present invention prepares silicon carbide microspheres through the high-temperature reaction of polycarbosilane and polyaniline under an inert atmosphere. As an important organosilicon polymer, polycarbosilane decomposes into silicon carbide nanocrystals during high-temperature pyrolysis, providing the main silicon source for silicon carbide. And as a conjugated polymer material with good conductivity, polyaniline decomposes into a carbon source under high-temperature reaction conditions. At the same time, the decomposition products released (such as ammonia or nitrogen oxides) can play a certain auxiliary role in the reaction system, reducing the surface energy during the pyrolysis process and promoting the uniform nucleation and growth of silicon carbide microspheres. This design ensures the particle size uniformity and surface smoothness of the product, and further optimizes the morphology and physical properties of the silicon carbide microspheres.

[0091] Silicon carbide is a typical high-performance ceramic material with a series of excellent physical and chemical properties. First of all, silicon carbide has excellent electrical insulation performance, and its high electrical breakdown strength makes it very suitable for use as a high-voltage-resistant insulating material; secondly, its high thermal conductivity enables it to effectively dissipate heat and reduce the risk of heat accumulation in the material; in addition, silicon carbide also has extremely high mechanical strength and hardness, which can significantly improve the mechanical properties of composite materials. These properties make silicon carbide an ideal filler for high-performance insulating composite materials, especially valuable in application scenarios with strict requirements for electrical and thermal properties such as new energy vehicle power battery packs.

[0092] However, unmodified silicon carbide shows some deficiencies in practical applications. First of all, silicon carbide has a relatively high surface chemical inertness and lacks active functional groups, resulting in weak interfacial bonding force between it and the polymer matrix (such as polysilazane). This weak interfacial interaction may cause interfacial delamination or stress concentration when the composite material is stressed or heated, significantly reducing the mechanical strength and electrical properties of the composite material. Secondly, due to the relatively large specific surface area and high surface energy of silicon carbide microspheres, they are prone to agglomeration in the polymer matrix, resulting in poor filler dispersion, and ultimately leading to uneven properties of the composite material, such as deviations in local thermal conductivity or dielectric properties.

[0093] Therefore, in the present invention, silicon carbide microspheres are modified by growing molybdenum disulfide on their surfaces. Molybdenum disulfide is a typical two-dimensional layered transition metal sulfide, which is widely used in the research and development of functional materials due to its unique crystal structure and physical and chemical properties. In particular, the layered structure of molybdenum disulfide is composed of three-layer atoms of sulfur-molybdenum-sulfur stacked by weak van der Waals forces, with ultra-thin two-dimensional characteristics and excellent lubricity. Molybdenum disulfide not only has relatively high thermal conductivity, but also has a large specific surface area and rich surface active sites, and these characteristics make it suitable as a functional coating for the surface modification of silicon carbide.

[0094] In the present invention, molybdenum disulfide nanosheets are uniformly deposited on the surface of silicon carbide microspheres through a hydrothermal reaction to construct a silicon carbide / molybdenum disulfide composite material with a core-shell structure. The hydrothermal reaction provides a high-temperature and high-pressure reaction environment, which can promote the reaction of ammonium heptamolybdate and sodium sulfide on the surface of silicon carbide to generate molybdenum disulfide nanosheets. Since the molybdenum disulfide generated under hydrothermal conditions has good crystallinity, its nanosheets are firmly attached to the surface of silicon carbide by chemical adsorption or physical bonding, ensuring the stability and uniformity of the composite material.

[0095] This core-shell structure design significantly enhances the performance of silicon carbide. First, the introduction of molybdenum disulfide effectively improves the thermal conductivity of silicon carbide because molybdenum disulfide itself has a high lateral thermal conductivity, and its layered structure can provide additional conduction paths for heat transfer. Second, the layered structure of molybdenum disulfide brings abundant surface active sites, including sulfur bonds and possible defect active sites, which improves the surface activity of silicon carbide and provides more binding sites for subsequent surface functionalization. In addition, the layered property of molybdenum disulfide also has good lubrication effects, which has a positive impact on the processing performance of the material and the interfacial stability of the composite material.

[0096] On this basis, the silicon carbide / molybdenum disulfide composite material is further subjected to surface coating treatment with organic boron to further improve its interfacial compatibility, electrical insulation and flame retardancy. Specifically, by reacting boron trifluoride ether complex and phenyltrimethoxysilane together on the surface of the silicon carbide / molybdenum disulfide composite material, a stable organic boron coating layer is formed. Boron trifluoride ether complex can react chemically with the exposed active sites on the surface of molybdenum disulfide to form stable chemical bonds. At the same time, phenyltrimethoxysilane forms a silicon-oxygen network on the material surface through hydrolysis and polycondensation reactions, and its phenyl structure can effectively enhance the hydrophobicity of the material, thereby improving the dispersibility and interfacial compatibility of the composite material in the polysilazane matrix.

[0097] The organic boron coating layer plays a role in enhancing multiple functions in the composite material. First, the introduction of its boron-oxygen bonds enhances the electrical insulation performance of the material, reduces the dielectric loss of the material, and thus improves the breakdown voltage performance of the composite material. Second, the presence of the organic boron layer significantly improves the flame retardancy of the material because boron elements can participate in charring and flame retardant reactions under high temperature conditions to inhibit the combustion behavior of the material. In addition, the chemical stability and hydrophobicity of the organic boron coating layer further improve the long-term stability of the composite material in complex usage environments.

[0098] In this invention, metal-organic supramolecular cages are synthesized by trimesic acid and zinc nitrate under solvothermal reaction conditions, providing a functionalized porous material basis for the development of high-performance insulating materials. Metal-organic supramolecular cages are a type of porous materials formed by the coordination of organic ligands and metal ions through coordination bonds, with highly designable, adjustable microstructures and excellent physical and chemical properties. In this invention, trimesic acid is used as a ligand, and its tricarboxyl structure provides multiple coordination sites for metal ions and can form a stable three-dimensional pore structure through coordination. Through solvothermal reaction conditions, the crystal structure of the metal-organic supramolecular cage is precisely regulated, and finally metal-organic supramolecular cages with high specific surface area and highly ordered pores are prepared.

[0099] Metal-organic supramolecular cages exhibit significant performance advantages in composite materials. First, their high specific surface area and porous structure provide more contact sites for interface regulation of composite materials, significantly enhancing the dielectric properties of composite materials. Second, their excellent chemical and thermal stability enables them to maintain structural integrity under high temperatures and complex environments, ensuring the long-term service performance of composite materials. In addition, the pore structure of metal-organic supramolecular cages can effectively reduce the dielectric loss of materials, thereby enhancing the breakdown voltage performance of composite materials. These advantages make metal-organic supramolecular cages important functional fillers for designing high-performance insulating materials.

[0100] However, unmodified metal-organic supramolecular cages still have some deficiencies in practical applications. First, the mechanical properties of metal-organic supramolecular cages are weak, and their framework structures are prone to local damage under external or thermal stress, which may lead to a decrease in the mechanical properties of composite materials. Second, due to the weak binding force and poor interfacial compatibility between the surface chemical structure of metal-organic supramolecular cages and the polymer matrix (such as polysilazane), such interfacial defects may cause stress concentration or interfacial delamination, affecting the overall performance of composite materials. In addition, the thermal conductivity of metal-organic supramolecular cages is generally low, making it difficult to meet the requirements of high-thermal-conductivity insulating materials, especially in applications such as new energy vehicle power battery packs that have strict requirements for thermal management capabilities.

[0101] To solve these problems, a series of targeted modification steps are designed in this invention to functionalize metal-organic supramolecular cages by introducing carbon nitride. Carbon nitride is a two-dimensional material with high thermal conductivity, chemical stability, and excellent surface activity, and its layered structure enables it to form a stable composite structure with the surface of metal-organic supramolecular cages. In this invention, by treating carbon nitride with concentrated nitric acid, active functional groups such as carboxyl and hydroxyl groups are introduced onto its surface. These functional groups can undergo chemical reactions with the ligand structure of metal-organic supramolecular cages, and carbon nitride is loaded onto the surface of metal-organic supramolecular cages through covalent bonds or hydrogen bonds to form a stable metal-organic supramolecular cage / carbon nitride composite structure.

[0102] The introduction of carbon nitride is of great significance for improving the performance of metal-organic supramolecular cages. First, the high thermal conductivity of carbon nitride significantly enhances the overall thermal conductivity of metal-organic supramolecular cages, providing a more efficient heat conduction path for composite materials. Second, the high mechanical strength and flexibility of carbon nitride effectively enhance the mechanical properties of metal-organic supramolecular cages, enabling them to better withstand external stress in composite materials. In addition, the composite structure formed between carbon nitride and the surface of metal-organic supramolecular cages significantly improves the interfacial binding force between the two, reducing interfacial defect problems, thereby enhancing the overall performance of composite materials.

[0103] On the basis of carbon nitride modification, the present invention further introduces a silica network structure onto the surface of the metal-organic supramolecular cage through the hydrolysis and polycondensation reaction of trifluoropropyltriethoxysilane. Trifluoropropyltriethoxysilane is a fluorinated silane coupling agent, and its hydrolysis and polycondensation reaction can form stable silicon-oxygen bond connections on the material surface. At the same time, its trifluoropropyl structure can significantly reduce the surface energy of the material, enhancing the hydrophobicity and chemical stability of the composite material. Through this step, the surface of the metal-organic supramolecular cage is not only further functionally modified, but also the dispersibility and interfacial compatibility of the material in the polysilazane matrix are significantly improved.

[0104] In the present invention, carbon nanotubes are introduced as functional fillers to significantly improve the mechanical properties, thermal conductivity and toughening effect of the composite material. Carbon nanotubes are a kind of nanomaterial with a hollow tubular structure, and their unique physical and chemical properties make them show great potential in various high-performance composite materials. First of all, carbon nanotubes have high strength and modulus, which can improve the mechanical properties of the composite material, especially in the matrix, they can effectively resist the action of external stress; secondly, carbon nanotubes have a high thermal conductivity, which can form an efficient thermal conduction channel in the composite material, thereby improving the thermal management ability of the material. In addition, due to the high aspect ratio of carbon nanotubes, they can form a uniformly distributed network structure in the matrix, playing a significant toughening role, effectively improving the toughness of the composite material and reducing the risk of brittle fracture.

[0105] However, unmodified carbon nanotubes face many problems in practical applications, which limit their wide application in the field of composite materials. First of all, the surface of carbon nanotubes has strong chemical inertness and lacks active functional groups, which makes it difficult to form a strong interfacial bond in the polymer matrix (such as polysilazane), thus affecting the interfacial strength and overall performance of the composite material. Secondly, due to the high van der Waals force on the surface of carbon nanotubes, they are prone to agglomeration in the matrix and difficult to achieve uniform dispersion, resulting in local non-uniformity of the filler distribution, thereby weakening the performance of the composite material. In addition, although the high conductivity of carbon nanotubes is an advantage in conductive composite materials, it may cause a decrease in dielectric properties in high-insulation materials, reducing the breakdown voltage and electrical insulation performance of the material. Therefore, to solve these key problems, the present invention has carried out multi-step modification treatment on carbon nanotubes to endow them with higher surface activity, more excellent interfacial bonding force and properties more suitable for the application of insulating materials.

[0106] First, the surface of carbon nanotubes is preliminarily activated by acid treatment. The acid treatment uses a mixed acid system of concentrated nitric acid and sulfuric acid. By utilizing the oxidation of strong acids, active functional groups such as hydroxyl and carboxyl groups are introduced onto the surface of carbon nanotubes. During the acid treatment process, the oxidant can destroy part of the π-bond structure of carbon nanotubes, forming polar functional groups at the tube wall and tube ends. These functional groups significantly improve the surface hydrophilicity and chemical activity of carbon nanotubes, thereby effectively improving their dispersibility in the matrix and providing more binding sites for subsequent chemical modification. After the activation treatment, the carbon nanotubes can not only be more evenly distributed in the polysilazane matrix, but also significantly improve the interfacial binding force with the matrix through surface polarity.

[0107] On the basis of acid treatment, in order to further improve the insulation performance and thermal stability of carbon nanotubes, the present invention introduces rare earth element lanthanum ions to modify them. Lanthanum ions form a stable rare earth oxide modification layer on the surface of carbon nanotubes through a coordination reaction with the carboxyl and hydroxyl groups introduced on the surface of carbon nanotubes. The introduction of lanthanum ions optimizes the properties of carbon nanotubes in many aspects. On the one hand, the rare earth oxide layer plays a shielding role in the conductivity of carbon nanotubes, significantly reducing its conductivity, thereby improving the breakdown voltage performance and electrical insulation of the composite material; on the other hand, the high thermal stability of lanthanum ions endows carbon nanotubes with stronger high-temperature resistance, enabling them to maintain the stability of structure and performance in high-temperature environments. In addition, the rare earth modification layer further enhances the interfacial interaction force between carbon nanotubes and the matrix, laying a foundation for subsequent composite modification.

[0108] In order to further improve the thermal conductivity and electrical insulation of carbon nanotubes, the present invention conducts composite modification on lanthanum-modified carbon nanotubes by introducing boron nitride. Boron nitride is a two-dimensional material with high thermal conductivity and high insulation. Its layered structure consists of nitrogen-boron planes bonded by strong covalent bonds and interlayer interactions bonded by weak van der Waals forces. After boron nitride is exfoliated, it forms a single-layer or few-layer structure and can be evenly attached to the surface of lanthanum-modified carbon nanotubes through electrostatic adsorption or chemical bonding. The introduction of boron nitride is of great significance in improving material properties. On the one hand, the high thermal conductivity of boron nitride significantly enhances the heat conduction ability of carbon nanotubes, and can construct a multi-dimensional heat conduction network in the composite material, thereby significantly improving the overall thermal conductivity of the composite material; on the other hand, the high insulation of boron nitride effectively reduces the conductivity of the composite material, further improving its breakdown strength and breakdown voltage performance. In addition, the two-dimensional structure of boron nitride can also enhance the interfacial stability of the composite material and reduce interfacial defects.

[0109] Finally, in order to optimize the dispersion and interfacial bonding properties of carbon nanotubes in the polysilazane matrix, the present invention uses 3-aminopropyltriethoxysilane to modify the surface of boron nitride composite carbon nanotubes. The ethoxy groups of 3-aminopropyltriethoxysilane can generate silanol groups after hydrolysis, and a silica network is formed on the surface of the carbon nanotubes through a polycondensation reaction. At the same time, its amino groups can form chemical bonds or hydrogen bonds with silicon or nitrogen atoms in the polysilazane matrix. Through the modification treatment of 3-aminopropyltriethoxysilane, the interfacial bonding force between the carbon nanotubes and the matrix is significantly improved, the interfacial compatibility is further enhanced, and the dispersion of the material in the matrix is optimized, avoiding the agglomeration of fillers. In addition, the silane modification also improves the processing performance of the composite material, comprehensively optimizing its mechanical properties and thermal stability.

[0110] Meanwhile, there is also a synergistic strengthening effect in the system: Silicon carbide itself has a relatively high thermal conductivity, but its heat conduction path mainly depends on the point contact between filler particles, and the heat conduction efficiency is limited. As a two-dimensional layered material, molybdenum disulfide has good heat conduction ability between its layers and provides a large lateral heat conduction path at the same time. When molybdenum disulfide is uniformly deposited on the surface of silicon carbide by hydrothermal method, a core-shell structure is formed, which not only improves the heat conduction efficiency of silicon carbide, but also significantly enhances the overall thermal conductivity of the composite material through the heat conduction network of the layered structure; Secondly, the surface of silicon carbide itself has strong chemical inertness and weak binding force with the matrix. The introduction of molybdenum disulfide provides more surface active sites (such as sulfhydryl groups and defect sites) through its layered nanosheets, and these sites can serve as binding points for subsequent surface modification, thereby improving the dispersion and interfacial binding force of silicon carbide in the matrix.

[0111] The synergistic effect between the silicon carbide / molybdenum disulfide composite and the organic boron coating layer is as follows: Silicon carbide and molybdenum disulfide itself have good insulation properties, but after being coated with organic boron, the high resistivity of the boron oxide layer further blocks the possible charge conduction paths, significantly reducing the dielectric loss of the composite material. Therefore, the combination of silicon carbide / molybdenum disulfide and the organic boron coating layer improves the breakdown voltage performance of the composite material, making it more suitable for insulation applications in high electric field environments; Secondly, the boron element in the organic boron coating layer can participate in the charring and flame retardant reactions under high temperature conditions to form a stable charred layer, which can effectively inhibit the flame propagation. At the same time, the physical barrier effect of the layered structure of molybdenum disulfide further enhances the flame retardant performance of the material, and the two form a synergistic flame retardant effect in a high temperature environment; In addition, the organic boron coating layer binds to the surface of molybdenum disulfide through chemical bonds, not only improving the surface stability of the composite material, but also enhancing the chemical resistance of the composite material in extreme environments (such as wet, high temperature or acid-base environments).

[0112] The synergistic enhancement effect between metal-organic supramolecular cages and carbon nitride is as follows: The porous structure of metal-organic supramolecular cages usually restricts their thermal conductivity. However, by modifying their surfaces with carbon nitride, the high thermal conductivity of this two-dimensional material can compensate for the insufficient thermal conductivity of metal-organic supramolecular cages. The thermal conduction paths formed by carbon nitride and the porous structure of metal-organic supramolecular cages act together to significantly improve the overall thermal conductivity of the composite material. The binding force between the surface of unmodified metal-organic supramolecular cages and the matrix is weak. After carbon nitride is treated with concentrated nitric acid, carboxyl and hydroxyl groups are introduced on its surface. These functional groups can chemically react with the ligands of metal-organic supramolecular cages to form a stable interfacial bond. In addition, the layered structure of carbon nitride can also relieve the interfacial stress concentration and further enhance the interfacial binding force. Metal-organic supramolecular cages have good insulation performance, but their pore structures may lead to the enhancement of the local electric field. The high insulation of carbon nitride can reduce this phenomenon and further improve the electric breakdown strength and dielectric stability of the composite material by forming a uniform coating on the surface of metal-organic supramolecular cages.

[0113] The combination of carbon nanotubes and metal-organic supramolecular cages plays a synergistic role by enhancing the mechanical and interfacial properties of the composite material: The high strength and high modulus of carbon nanotubes can enhance the overall mechanical properties of the composite material, while the porous structure of metal-organic supramolecular cages plays a buffering role by absorbing stress. The combination of the two enables the composite material to have both high strength and high toughness. The porous structure of metal-organic supramolecular cages provides more binding sites for carbon nanotubes, and the high aspect ratio of carbon nanotubes helps to form a continuous filler network in the matrix, thereby improving the dispersibility and interfacial binding force of the composite material.

[0114] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0115] In the present invention, silicon carbide microspheres are prepared by the reaction of polycarbosilane and polyaniline in a high-temperature inert atmosphere. Polycarbosilane provides a silicon source, and polyaniline provides a carbon source and auxiliary decomposition products, ensuring the particle size uniformity and surface smoothness of the silicon carbide microspheres. To improve the problems of poor chemical inertness, poor dispersibility, and insufficient interfacial binding force on the surface of silicon carbide, molybdenum disulfide is grown on its surface by a hydrothermal method to form a core-shell structured silicon carbide / molybdenum disulfide composite material, further improving the thermal conductivity and surface activity. At the same time, through the coating treatment with boron trifluoride diethyl ether complex and phenyltrimethoxysilane, the electrical insulation, flame retardancy, and environmental stability of the composite material are significantly enhanced, laying a foundation for the development of high-performance insulating materials.

[0116] The present invention prepares a metal-organic supramolecular cage by reacting trimesic acid with zinc nitrate and uses it as a functional filler for high-performance insulating materials. The metal-organic supramolecular cage significantly improves the dielectric properties and breakdown voltage properties of the composite material due to its high specific surface area and adjustable microstructure, but its mechanical properties and thermal conductivity are insufficient. The present invention modifies the metal-organic supramolecular cage by introducing carbon nitride. The high thermal conductivity and chemical stability of carbon nitride significantly compensate for the deficiencies of the metal-organic supramolecular cage, and at the same time, its surface active functional groups bind to the surface of the metal-organic supramolecular cage, enhancing the interfacial binding force. In addition, through the surface modification of 3,3,3-trifluoropropyltriethoxysilane, the dispersion and interfacial compatibility of the metal-organic supramolecular cage in the matrix are further optimized;

[0117] Similarly, in the present invention, carbon nanotubes, as fillers with high strength and high thermal conductivity, are introduced to enhance the mechanical properties and thermal conductivity of the composite material. However, the unmodified carbon nanotubes have strong surface chemical inertness, poor dispersion, and high conductivity. In the present invention, hydroxyl and carboxyl groups are introduced on their surface through acid treatment, improving their surface activity and dispersion. Subsequently, through lanthanum ion modification, a rare earth oxide layer is formed on the surface of the carbon nanotubes, reducing their conductivity and improving their high-temperature resistance. Further, boron nitride is compounded with lanthanum-modified carbon nanotubes, significantly improving the thermal conductivity and insulation performance of the composite material. Finally, through the surface modification of 3-aminopropyltriethoxysilane, the interfacial binding force of the carbon nanotubes and their uniform dispersion in the matrix are further improved;

[0118] The present invention significantly improves the performance of the composite material through the synergistic effect among multiple components. The core-shell structure of silicon carbide and molybdenum disulfide enhances the thermal conductivity and interfacial binding force, and the organic boron coating further improves the electrical insulation and flame retardancy. The combination of the metal-organic supramolecular cage and carbon nitride improves the thermal conductivity, interfacial binding force, and electrical insulation, while the combination of carbon nanotubes and the metal-organic supramolecular cage significantly enhances the mechanical properties and dispersion of the composite material. These synergistic effects optimize the thermal, electrical, and mechanical properties of the material. Description of the Drawings

[0119] Figure 1 It is a scanning electron microscope image of the silicon carbide / molybdenum disulfide composite material provided in Example 1 of the present invention;

[0120] Figure 2 It is a transmission electron microscope image of the silicon carbide / molybdenum disulfide composite material provided in Example 1 of the present invention;

[0121] Figure 3 It is a transmission electron microscope image of the carbon nitride-modified metal-organic supramolecular cage provided in Example 1 of the present invention;

[0122] Figure 4 It is a scanning electron microscope image of the boron nitride / lanthanum-modified carbon nanotubes provided in Example 1 of the present invention. Detailed implementation manners

[0123] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments described herein are specific specific implementation manners of the present invention and are used to illustrate the concept of the present invention; these descriptions are all explanatory and exemplary and should not be construed as limiting the implementation manner of the present invention and the protection scope of the present invention. Except for the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include technical solutions that make any obvious substitutions and modifications to the embodiments described herein.

[0124] The chemical reagents used in the embodiments and comparative examples of the present invention are all commercially available products and have not been further purified or processed.

[0125] Example 1

[0126] This example provides a high voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy vehicle and a preparation method thereof. The preparation method specifically includes the following steps:

[0127] S11: Mix polycarbosilane and polyaniline in a mass ratio of 1:11, react at a constant temperature of 1450 °C for 2.8 h in an inert atmosphere, then cool and filter to obtain a first product. Immerse it in a mixed acid solution for 5 h, centrifuge, wash and dry to obtain silicon carbide microspheres, where the volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is 2.7:1; the mass ratio of the first product to the mixed acid solution is 1:24;

[0128] S12: Disperse the silicon carbide microspheres in deionized water at a mass fraction of 1 wt.%, add ammonium heptamolybdate and sodium sulfide after ultrasonic dispersion, and then carry out a hydrothermal reaction at 174 °C for 12 h, where the molar ratio of ammonium heptamolybdate to sodium sulfide is 1:2; the mass ratio of silicon carbide to ammonium heptamolybdate is 1:0.25; centrifuge, wash and dry to obtain a silicon carbide / molybdenum disulfide composite material; Figure 1 As its scanning electron microscope image, it can be observed that molybdenum disulfide nanosheets are uniformly compounded on the surface of the silicon carbide microspheres. Figure 2 As its transmission electron microscope image, an obvious core-shell structure can be observed, indicating that molybdenum disulfide nanosheets are uniformly attached to the surface of the silicon carbide microspheres.

[0129] S13: Dissolve boron trifluoride ether complex and phenyltrimethoxysilane in tetrahydrofuran at a molar ratio of 1.1:1 and stir for 70 min to obtain a modified solution. The total mass fraction of boron trifluoride ether complex and phenyltrimethoxysilane in the modified solution is 7 wt.%. Add silicon carbide / molybdenum disulfide composite material to obtain reaction solution A. The mass ratio of silicon carbide / molybdenum disulfide composite material to the modified solution is 1:20. Stir at a constant temperature of 60 °C for 6 h and then cure at 270 °C for 2 h to obtain an organoboron-coated silicon carbide / molybdenum disulfide composite material;

[0130] S21: Dissolve trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water at a molar ratio of 1:15. The volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 4.7:1. The total concentration of trimesic acid and zinc nitrate hexahydrate in the mixed solution is 0.07 M. Perform a solvothermal reaction at 120 °C for 47 h, filter and wash to obtain a metal-organic supramolecular cage;

[0131] S22: Calcinate melamine at 550 °C for 4 h to obtain carbon nitride. Add it to concentrated nitric acid at a mass fraction of 3 wt.% and reflux. The reflux temperature is 120 °C and the time is 8 h. Filter, wash and dry to obtain modified carbon nitride. Disperse the modified carbon nitride and the metal-organic supramolecular cage in N,N-dimethylformamide at a mass ratio of 1.1:1. The mass fraction of the modified carbon nitride is 1.6 wt.%. After mixing evenly, perform a solvothermal reaction at 130 °C for 12 h, filter, wash and dry to obtain a carbon nitride-modified metal-organic supramolecular cage; Figure 3 The figure is its transmission electron micrograph. It can be observed that the metal-organic supramolecular cage has a spherical or nanocage-like structure, and there is a relatively light flaky distribution on its outer layer. Different contrast regions indicate that there is a relatively clear phase interface between the supramolecular cage and the carbon nitride layer, indicating the uniform coating of the supramolecular cage by carbon nitride modification.

[0132] S23: Disperse the carbon nitride-modified metal-organic supramolecular cage in anhydrous toluene at a mass fraction of 1.8 wt.%, add 3-trifluoropropyltriethoxysilane. The feeding amount of 3-trifluoropropyltriethoxysilane accounts for 5% of the mass of the carbon nitride-modified metal-organic supramolecular cage. Reflux at 118 °C for 6 h, centrifuge, wash and dry to obtain a pretreated product, and vacuum cure at 130 °C for 2 h to obtain a composite-modified metal-organic supramolecular cage;

[0133] S31: Modify carbon nanotubes by stirring them in a modified acid solution at 85 °C for 5 h to obtain modified carbon nanotubes. In the modified acid solution, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3.7:1, and the mass ratio of carbon nanotubes to the modified acid solution is 1:25. Disperse the modified carbon nanotubes in a lanthanum nitrate solution with a concentration of 0.15 M. The mass ratio of lanthanum nitrate to the modified carbon nanotubes is 1:10. Add sodium hydroxide to adjust the pH to 8 to obtain reaction solution B. Heat-treat it at 495 °C for 1.5 h under an argon atmosphere, filter, wash, and dry to obtain lanthanum-modified carbon nanotubes;

[0134] S32: Ultrasonically exfoliate hexagonal boron nitride in N-methylpyrrolidone. The concentration of hexagonal boron nitride in N-methylpyrrolidone is 0.7 mg / mL. Centrifuge to collect the supernatant for later use. Disperse the lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion. The concentration of lanthanum-modified carbon nanotubes in the first dispersion is 1.7 mg / mL. Mix it with the supernatant in a mass ratio of 1.5:1 and react for 2.7 h, then perform vacuum filtration, pre-dry at 77 °C for 3 h, and heat-treat at 290 °C for 25 min to obtain boron nitride / lanthanum-modified carbon nanotubes; Figure 4 This is its scanning electron microscope image. It can be seen that the surface of the carbon nanotubes is coated with boron nitride lamellar structures in the form of flakes.

[0135] S33: Disperse the boron nitride / lanthanum-modified carbon nanotubes in absolute ethanol at a mass fraction of 2.6 wt.%. Add 3-aminopropyltriethoxysilane with a dosage of 5% of the mass of the boron nitride / lanthanum-modified carbon nanotubes and triethylamine with a dosage of 0.5% of the mass of the boron nitride / lanthanum-modified carbon nanotubes. After mixing evenly, react at a constant temperature of 55 °C for 2.7 h, filter, wash, pre-dry at 77 °C for 2 h, and then cure at 144 °C for 2.8 h to obtain the composite-modified lanthanum-modified carbon nanotubes;

[0136] A1: Disperse polysilazane in absolute toluene at a mass fraction of 20 wt.%. After dispersing evenly, sequentially add an organoboron-coated silicon carbide / molybdenum disulfide composite material, a composite-modified metal-organic supramolecular cage, the composite-modified lanthanum-modified carbon nanotubes, a cross-linking agent vinyltrimethoxysilane, and a flame retardant aluminum hydroxide, and stir to obtain a mixed solution. Pour it into a mold to remove bubbles, pre-cure at 77 °C for 3.6 h, heat-cure at 230 °C under an inert atmosphere for 2 h, and then cool naturally to obtain a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs. The mass ratio of polysilazane, the organoboron-coated silicon carbide / molybdenum disulfide composite material, the composite-modified metal-organic supramolecular cage, the composite-modified lanthanum-modified carbon nanotubes, the cross-linking agent, and the flame retardant is 82:35:38:30:4.6:3.

[0137] Example 2

[0138] This embodiment provides a high-voltage-resistant polysilazane-based insulating material for a power battery pack of a new energy vehicle and a preparation method thereof. The preparation method specifically includes the following steps:

[0139] S11: Mix polycarbosilane and polyaniline at a mass ratio of 1:1.15, react at a constant temperature of 1480 °C for 2.6 h in an inert atmosphere, then cool and filter to obtain a first product. Immerse the first product in a mixed acid solution for 6 h, centrifuge, wash, and dry to obtain silicon carbide microspheres, where the volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is 3:1; the mass ratio of the first product to the mixed acid solution is 1:30;

[0140] S12: Disperse the silicon carbide microspheres in deionized water at a mass fraction of 1.1 wt . %, ultrasonically disperse, add ammonium heptamolybdate and sodium sulfide, and then carry out a hydrothermal reaction at 180 °C for 13 h, where the molar ratio of ammonium heptamolybdate to sodium sulfide is 1:3; the mass ratio of silicon carbide to ammonium heptamolybdate is 1:0.3; centrifuge, wash, and dry to obtain a silicon carbide / molybdenum disulfide composite;

[0141] S13: Dissolve boron trifluoride diethyl ether complex and phenyltrimethoxysilane in tetrahydrofuran at a molar ratio of 0.9:1 and stir for 80 min to obtain a modified solution, where the total mass fraction of boron trifluoride diethyl ether complex and phenyltrimethoxysilane in the modified solution is 8 wt.%. Add the silicon carbide / molybdenum disulfide composite to obtain reaction solution A, where the mass ratio of the silicon carbide / molybdenum disulfide composite to the modified solution is 1:25, stir at a constant temperature of 67 °C for 6.7 h, and then cure at 260 °C for 2.3 h to obtain an organoboron-coated silicon carbide / molybdenum disulfide composite;

[0142] S21: Dissolve trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water at a molar ratio of 1:18, where the volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 5:1, and the total concentration of trimesic acid and zinc nitrate hexahydrate in the mixed solution is 0.1 M. Carry out a solvothermal reaction at 130 °C for 50 h, filter and wash to obtain a metal-organic supramolecular cage;

[0143] S22: Calcinate melamine at 570 °C for 5 h to obtain carbon nitride, add it to concentrated nitric acid at a mass fraction of 4 wt.% and carry out a reflux reaction, where the reflux reaction temperature is 130 °C and the time is 9 h. Filter, wash, and dry to obtain modified carbon nitride. Disperse the modified carbon nitride and the metal-organic supramolecular cage in N,N-dimethylformamide at a mass ratio of 1:1, where the mass fraction of the modified carbon nitride is 2 wt.%. After mixing evenly, carry out a solvothermal reaction at 150 °C for 13 h, filter, wash, and dry to obtain a carbon nitride-modified metal-organic supramolecular cage;

[0144] S23: Disperse carbon nitride modified metal-organic supramolecular cages at a mass fraction of 2 wt . % in anhydrous toluene, add trifluoropropyltriethoxysilane, where the feeding amount of trifluoropropyltriethoxysilane accounts for 5.6% of the mass of carbon nitride modified metal-organic supramolecular cages, reflux and react at 123 °C for 7 h, centrifuge, wash, and dry to obtain a pretreatment product, and vacuum cure at 140 °C for 2.3 h to obtain a composite modified metal-organic supramolecular cage;

[0145] S31: Stir and modify carbon nanotubes in a modified acid solution at 90 °C for 6 h to obtain modified carbon nanotubes, where the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the modified acid solution is 4:1, and the mass ratio of carbon nanotubes to the modified acid solution is 1:30. Disperse the modified carbon nanotubes in a lanthanum nitrate solution with a concentration of 0.12 M, where the mass ratio of lanthanum nitrate to the modified carbon nanotubes is 1:9, add sodium hydroxide to adjust the pH to 9 to obtain reaction solution B, heat-treat at 510 °C for 2 h in an argon atmosphere, filter, wash, and dry to obtain lanthanum-modified carbon nanotubes;

[0146] S32: Ultrasonically exfoliate hexagonal boron nitride in N-methylpyrrolidone, where the concentration of hexagonal boron nitride in N-methylpyrrolidone is 0.9 mg / mL, centrifuge and collect the supernatant for standby. Disperse the lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion, where the concentration of lanthanum-modified carbon nanotubes in the first dispersion is 1.2 mg / mL, mix with the supernatant at a mass ratio of 1.2:1 and react for 3 h, then vacuum filter, pre-dry at 73 °C for 3.4 h, and heat-treat at 300 °C for 35 min to obtain boron nitride / lanthanum-modified carbon nanotubes;

[0147] S33: Disperse boron nitride / lanthanum-modified carbon nanotubes at a mass fraction of 3 wt.% in absolute ethanol, add 3-aminopropyltriethoxysilane with a feeding amount of 4% of the mass of boron nitride / lanthanum-modified carbon nanotubes and triethylamine with a feeding amount of 1% of the mass of boron nitride / lanthanum-modified carbon nanotubes, mix evenly, react at a constant temperature of 58 °C for 2.3 h, filter, wash, pre-dry at 73 °C for 3 h, and then cure at 148 °C for 3 h to obtain a composite modified lanthanum-modified carbon nanotubes;

[0148] A1: Disperse polysilazane in anhydrous toluene at a mass fraction of 24 wt.%, and after uniform dispersion, successively add organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, cross-linking agent vinyltriethoxysilane and flame retardant magnesium hydroxide, stir to obtain a mixed solution, pour it into a mold for defoaming, pre-cure at 73 °C for 3.4 h, thermally cure at 240 °C in an inert atmosphere for 2.3 h, and then naturally cool to obtain a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs, where the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, cross-linking agent and flame retardant is 80:37:40:25:4:3.5.

[0149] Example 3

[0150] This example provides a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs and its preparation method. The preparation method specifically includes the following steps:

[0151] S11: Mix polycarbosilane and polyaniline at a mass ratio of 1:1, react at a constant temperature of 1400 °C in an inert atmosphere for 2 h, then cool and filter to obtain a first product, soak it in a mixed acid solution for 4 h, centrifuge, wash and dry to obtain silicon carbide microspheres, where the volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is 2:1; the mass ratio of the first product to the mixed acid solution is 1:20;

[0152] S12: Disperse the silicon carbide microspheres at a mass fraction of 0.8 wt . % in deionized water, ultrasonically disperse, add ammonium heptamolybdate and sodium sulfide, and then carry out hydrothermal reaction at 170 °C for 10 h, where the molar ratio of ammonium heptamolybdate to sodium sulfide is 1:2.6; the mass ratio of silicon carbide to ammonium heptamolybdate is 1:0.2; centrifuge, wash and dry to obtain silicon carbide / molybdenum disulfide composite material;

[0153] S13: Dissolve boron trifluoride diethyl ether complex and phenyltrimethoxysilane at a molar ratio of 1:1 in tetrahydrofuran and stir for 60 min to obtain a modified solution, where the total mass fraction of boron trifluoride diethyl ether complex and phenyltrimethoxysilane in the modified solution is 5 wt.%, add the silicon carbide / molybdenum disulfide composite material to obtain reaction solution A, where the mass ratio of the silicon carbide / molybdenum disulfide composite material to the modified solution is 1:15, stir at a constant temperature of 63 °C for 5 h, and then cure at 250 °C for 1.5 h to obtain organoboron-coated silicon carbide / molybdenum disulfide composite material;

[0154] S21: Dissolve trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water at a molar ratio of 1:1, where the volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 4:1, and the total concentration of trimesic acid and zinc nitrate hexahydrate in the mixed solution is 0.05 M. Carry out a solvothermal reaction at 110 °C for 45 h, filter and wash to obtain a metal-organic supramolecular cage;

[0155] S22: Calcinate melamine at 530 °C for 3 h to obtain carbon nitride, add it to concentrated nitric acid at a mass fraction of 2 wt.% and reflux for reaction, where the reflux temperature is 128 °C and the time is 7 h. Filter, wash and dry to obtain modified carbon nitride. Disperse the modified carbon nitride and the metal-organic supramolecular cage in N,N-dimethylformamide at a mass ratio of 0.8:1, where the mass fraction of the modified carbon nitride is 1 wt.%. After mixing evenly, carry out a solvothermal reaction at 140 °C for 10 h, filter, wash and dry to obtain carbon nitride-modified metal-organic supramolecular cage;

[0156] S23: Disperse the carbon nitride-modified metal-organic supramolecular cage at a mass fraction of 1 wt . % in anhydrous toluene, add 3-trifluoropropyltriethoxysilane, where the feeding amount of 3-trifluoropropyltriethoxysilane accounts for 4% of the mass of the carbon nitride-modified metal-organic supramolecular cage. Carry out a reflux reaction at 115 °C for 5 h, centrifuge, wash and dry to obtain a pretreated product, and carry out vacuum curing at 120 °C for 1.5 h to obtain a composite-modified metal-organic supramolecular cage;

[0157] S31: Stir and modify carbon nanotubes in a modified acid solution at 80 °C for 6.5 h to obtain modified carbon nanotubes, where the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the modified acid solution is 3:1, and the mass ratio of carbon nanotubes to the modified acid solution is 1:20. Disperse the modified carbon nanotubes in a lanthanum nitrate solution with a concentration of 0.1 M, and the mass ratio of lanthanum nitrate to the modified carbon nanotubes is 1:8. Add sodium hydroxide to adjust the pH to 8.8 to obtain reaction solution B. Carry out heat treatment at 480 °C for 1 h in an argon atmosphere, filter, wash and dry to obtain lanthanum-modified carbon nanotubes;

[0158] S32: Ultrasonically exfoliate hexagonal boron nitride in N-methylpyrrolidone, where the concentration of hexagonal boron nitride in N-methylpyrrolidone is 0.5 mg / mL, centrifuge and collect the supernatant for standby. Disperse the lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion, where the concentration of the lanthanum-modified carbon nanotubes in the first dispersion is 1 mg / mL. Mix and react with the supernatant at a mass ratio of 1.6:1 for 2 h, then carry out vacuum filtration, pre-dry at 70 °C for 3.8 h, and heat-treat at 280 °C for 28 min to obtain boron nitride / lanthanum-modified carbon nanotubes;

[0159] S33: Disperse boron nitride / lanthanum modified carbon nanotubes in absolute ethanol at a mass fraction of 2 wt.%, add 3-aminopropyltriethoxysilane with a feed amount of 5.4% of the mass of boron nitride / lanthanum modified carbon nanotubes and triethylamine with a feed amount of 0.8% of the mass of boron nitride / lanthanum modified carbon nanotubes. After mixing evenly, react at a constant temperature of 50 °C for 2 h, filter, wash, pre-dry at 70 °C for 2.7 h, and then cure at 140 °C for 2 h to obtain composite modified lanthanum modified carbon nanotubes;

[0160] A1: Disperse polysilazane in absolute toluene at a mass fraction of 22 wt.%. After dispersing evenly, successively add organoboron-coated silicon carbide / molybdenum disulfide composite material, composite modified metal-organic supramolecular cage, composite modified lanthanum modified carbon nanotubes, cross-linking agent vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and flame retardants aluminum hydroxide and ammonium polyphosphate, stir to obtain a mixed solution, pour it into a mold to remove bubbles, pre-cure at 70 °C for 3 h, thermally cure at 200 °C in an inert atmosphere for 2.7 h, and then naturally cool to obtain a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs, where the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite modified metal-organic supramolecular cage, composite modified lanthanum modified carbon nanotubes, cross-linking agent, and flame retardant is 83:30:35:32:4.8:3.7.

[0161] Example 4

[0162] This example provides a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs and its preparation method. The preparation method specifically includes the following steps:

[0163] S11: Mix polycarbosilane and polyaniline at a mass ratio of 1:1.2, react at a constant temperature of 1500 °C in an inert atmosphere for 3 h, then cool and filter to obtain a first product. Immerse it in a mixed acid solution for 5.6 h, centrifuge, wash, and dry to obtain silicon carbide microspheres, where the volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is 2.3:1; the mass ratio of the first product to the mixed acid solution is 1:26;

[0164] S12: Disperse silicon carbide microspheres in deionized water at a mass fraction of 1.2 wt . %, ultrasonically disperse, add ammonium heptamolybdate and sodium sulfide, and then carry out a hydrothermal reaction at 178 °C for 14 h, where the molar ratio of ammonium heptamolybdate to sodium sulfide is 1:2.3; the mass ratio of silicon carbide to ammonium heptamolybdate is 1:0.28; centrifuge, wash, and dry to obtain silicon carbide / molybdenum disulfide composite material;

[0165] S13: Dissolve boron trifluoride ether complex and phenyltrimethoxysilane in tetrahydrofuran at a molar ratio of 1.2:1 and stir for 90 min to obtain a modified solution. The total mass fraction of boron trifluoride ether complex and phenyltrimethoxysilane in the modified solution is 6 wt.%. Add silicon carbide / molybdenum disulfide composite to obtain reaction solution A. The mass ratio of silicon carbide / molybdenum disulfide composite to the modified solution is 1:22. Stir at a constant temperature of 70 °C for 7 h and then cure at 280 °C for 2.5 h to obtain silicon carbide / molybdenum disulfide composite coated with organic boron;

[0166] S21: Dissolve trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water at a molar ratio of 1:2. The volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 4.5:1. The total concentration of trimesic acid and zinc nitrate hexahydrate in the mixed solution is 0.09 M. Carry out solvothermal reaction at 125 °C for 48 h, filter and wash to obtain a metal-organic supramolecular cage;

[0167] S22: Calcinate melamine at 580 °C for 4.5 h to obtain carbon nitride. Add it to concentrated nitric acid at a mass fraction of 5 wt.% and carry out reflux reaction. The reflux reaction temperature is 123 °C and the time is 7.8 h. Filter, wash and dry to obtain modified carbon nitride. Disperse the modified carbon nitride and the metal-organic supramolecular cage in N,N-dimethylformamide at a mass ratio of 1.2:1. The mass fraction of the modified carbon nitride is 1.2 wt.%. After mixing evenly, carry out solvothermal reaction at 145 °C for 14 h, filter, wash and dry to obtain carbon nitride-modified metal-organic supramolecular cage;

[0168] S23: Disperse the carbon nitride-modified metal-organic supramolecular cage in anhydrous toluene at a mass fraction of 1.2 wt . %. Add 3,3,3-trifluoropropyltriethoxysilane. The feeding amount of 3,3,3-trifluoropropyltriethoxysilane accounts for 6% of the mass of the carbon nitride-modified metal-organic supramolecular cage. Carry out reflux reaction at 125 °C for 6.7 h. After centrifugation, washing and drying, obtain a pretreatment product, and carry out vacuum curing at 134 °C for 2.5 h to obtain a composite-modified metal-organic supramolecular cage;

[0169] S31: Stir and modify carbon nanotubes in a modified acid solution at 88 °C for 7 h to obtain modified carbon nanotubes. The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the modified acid solution is 3.4:1. The mass ratio of carbon nanotubes to the modified acid solution is 1:28. Disperse the modified carbon nanotubes in a lanthanum nitrate solution with a concentration of 0.2 M. The mass ratio of lanthanum nitrate to the modified carbon nanotubes is 1:12. Add sodium hydroxide to adjust the pH to 8.3 to obtain reaction solution B. Carry out heat treatment at 520 °C for 1.2 h in an argon atmosphere, filter, wash and dry to obtain lanthanum-modified carbon nanotubes;

[0170] S32: Ultrasonically exfoliate hexagonal boron nitride in N-methylpyrrolidone, where the concentration of hexagonal boron nitride in N-methylpyrrolidone is 1 mg / mL. Centrifuge to collect the supernatant for later use. Disperse lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion, where the concentration of lanthanum-modified carbon nanotubes in the first dispersion is 2 mg / mL. Mix it with the supernatant in a mass ratio of 1.8:1 and react for 2.3 h, then perform vacuum filtration, pre-dry at 80 °C for 4 h, and heat-treat at 320 °C for 30 min to obtain boron nitride / lanthanum-modified carbon nanotubes;

[0171] S33: Disperse boron nitride / lanthanum-modified carbon nanotubes in absolute ethanol at a mass fraction of 2.3 wt.%. Add 3-aminopropyltriethoxysilane with a feeding amount of 6% of the mass of boron nitride / lanthanum-modified carbon nanotubes and triethylamine with a feeding amount of 0.92% of the mass of boron nitride / lanthanum-modified carbon nanotubes. After mixing evenly, react at a constant temperature of 60 °C for 3 h, filter, wash, pre-dry at 80 °C for 2.3 h, and then cure at 150 °C for 2.3 h to obtain composite-modified lanthanum-modified carbon nanotubes;

[0172] A1: Disperse polysilazane in anhydrous toluene at a mass fraction of 25 wt.%. After dispersing evenly, sequentially add organoboron-coated silicon carbide / molybdenum disulfide composite materials, composite-modified metal-organic supramolecular cages, composite-modified lanthanum-modified carbon nanotubes, crosslinking agents vinyltrimethoxysilane, vinyltriethoxysilane, and flame retardants aluminum hydroxide and magnesium hydroxide, and stir to obtain a mixed solution. Pour it into a mold to remove bubbles, pre-cure at 80 °C for 4 h, heat-cure at 250 °C in an inert atmosphere for 3 h, and then naturally cool to obtain a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs, where the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite materials, composite-modified metal-organic supramolecular cages, composite-modified lanthanum-modified carbon nanotubes, crosslinking agents, and flame retardants is 85:40:45:35:5:4.

[0173] Comparative Example 1

[0174] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for new energy vehicle power battery packs. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite materials, composite-modified metal-organic supramolecular cages, composite-modified lanthanum-modified carbon nanotubes, crosslinking agents, and flame retardants is 82:45:38:30:4.6:3.

[0175] Comparative Example 2

[0176] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, crosslinking agent, and flame retardant is 82:20:38:30:4.6:3.

[0177] Comparative Example 3

[0178] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, crosslinking agent, and flame retardant is 82:45:48:30:4.6:3.

[0179] Comparative Example 4

[0180] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, crosslinking agent, and flame retardant is 82:45:30:30:4.6:3.

[0181] Comparative Example 5

[0182] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, crosslinking agent, and flame retardant is 82:45:30:40:4.6:3.

[0183] Comparative Example 6

[0184] This comparative example provides a high-voltage-resistant polysilazane-based insulating material for a new energy vehicle power battery pack. The difference from Example 1 is that in A1, the mass ratio of polysilazane, organoboron-coated silicon carbide / molybdenum disulfide composite material, composite-modified metal-organic supramolecular cage, composite-modified lanthanum-modified carbon nanotubes, crosslinking agent, and flame retardant is 82:45:48:20:4.6:3.

[0185] Perform performance tests on the high-voltage-resistant polysilazane-based insulating materials for the new energy vehicle power battery packs in the above Examples 1-4 and Comparative Examples 1-6. The specific process is as follows:

[0186] The material was prepared into circular specimens with a thickness of 0.3 mm and a diameter of 90 mm, and tested by a computer-controlled voltage breakdown tester in the DC breakdown mode. The voltage increase rate was 1 kV / mm, and the average value of 5 tests was taken as the high-voltage DC breakdown strength value;

[0187] The volume resistivity of the test sample was measured according to GB / T 31838.2-2019;

[0188] The test results are shown in Table 1.

[0189] Table 1: Test results of the insulation material properties of Examples 1-4 and Comparative Examples 1-6

[0190]

[0191] From the test results of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that when the addition amount of the organoboron-coated silicon carbide / molybdenum disulfide composite material is too high, the spacing between silicon carbide particles decreases, which is easy to form a conductive path. At the same time, the interlayer stacking of molybdenum disulfide on its surface increases, thereby increasing the probability of electron transition, resulting in a decrease in the breakdown field strength and volume resistivity of the insulating material; when its addition amount is insufficient, the overall heat diffusion is limited, and the electric field concentration in the local area causes the macroscopic breakdown value to be pulled down, but the lack of overall polar groups makes the insulating network relatively densified, thereby increasing the volume resistivity.

[0192] From the test results of Example 1, Comparative Example 3, and Comparative Example 4, it can be seen that when the addition amount of the composite modified metal-organic supramolecular cage is too much, the metal center of the metal-organic supramolecular cage forms a local conductive region, and at the same time, the excessive carbon nitride modification layer leads to enhanced polarization, resulting in a decrease in the breakdown field strength and volume resistivity; when its addition amount is insufficient, due to the insufficient number of charge traps, electrons are easy to migrate, and the sparse distribution of the cage structure of the metal-organic supramolecular cage causes uneven electric field distribution, resulting in a decrease in the breakdown field strength and volume resistivity.

[0193] From the test results of Example 1, Comparative Example 5, and Comparative Example 6, it can be seen that when the addition amount of the composite modified lanthanum-modified carbon nanotubes is too much, the carbon nanotubes are easy to form a conductive network, and the excessive lanthanum ions lead to enhanced local polarization. At the same time, the decrease in the gap between boron nitride sheets increases the probability of electron tunneling, resulting in a significant decrease in the breakdown field strength and a decrease in the volume resistivity; when its addition amount is insufficient, due to the insufficient density of deep-level traps of lanthanum ions and the incomplete synergistic network of boron nitride / lanthanum-modified carbon nanotubes, the charge modulation ability is weakened, resulting in a decrease in the breakdown field strength and an increase in the volume resistivity.

[0194] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A method for preparing a high-voltage polysilazane-based insulating material for a new energy vehicle power battery pack, characterized in that: The preparation method comprises: A1: Disperse polysilazane in anhydrous toluene, and after uniform dispersion, add organic boron-coated silicon carbide / molybdenum disulfide composite materials, composite modified metal organic supramolecular cages, composite modified lanthanum-modified carbon nanotubes, cross-linking agents and flame retardants in sequence, stir to obtain a mixed solution, pour the mixed solution into a mold for degassing, pre-curing, heat curing under an inert atmosphere, and then naturally cool to obtain a high-voltage polysilazane-based insulating material for new energy vehicle power battery packs.

2. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 1, characterized in that: In A1: The mass fraction of the polysilazane in anhydrous toluene is 20-25wt.%; The crosslinking agent is any one of vinyl trimethoxy silane, vinyl triethoxy silane or γ-methacryloxypropyl trimethoxy silane or a combination of two; The flame retardant is any one of aluminum hydroxide, magnesium hydroxide or ammonium polyphosphate or a combination of two thereof.

3. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 1, characterized in that: The preparation method of the organic boron-coated silicon carbide / molybdenum disulfide composite material is as follows: S11: mixing polycarbosilane and polyaniline, reacting at a constant temperature under an inert atmosphere, cooling, filtering to obtain a first product, soaking the first product in a mixed acid solution, washing by centrifugation, and drying to obtain silicon carbide microspheres; S12: dispersing silicon carbide microspheres in deionized water, adding ammonium heptamolybdate and sodium sulfide after ultrasonic dispersion, and then hydrothermally reacting, centrifuging, washing, and drying to obtain a silicon carbide / molybdenum disulfide composite material; S13: dissolving a boron trifluoride ether complex and phenyltrimethoxysilane in tetrahydrofuran and stirring to obtain a modified solution, adding a silicon carbide / molybdenum disulfide composite material to obtain a reaction solution A, stirring at a constant temperature and then curing to obtain an organic boron-coated silicon carbide / molybdenum disulfide composite material.

4. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 3, characterized in that: In S11: The mass ratio of the polycarbosilane to the polyaniline is 1:(1-1.2); The volume ratio of hydrofluoric acid to nitric acid in the mixed acid solution is (2-3):1; The mass ratio of the first product to the mixed acid solution is 1:(20-30); In S12: The molar ratio of ammonium heptamolybdate to sodium sulfide is 1:(2-3); The mass ratio of the silicon carbide to ammonium heptamolybdate is 1:(0.2-0.3).

5. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 3, characterized in that: In S13: The molar ratio of the boron trifluoride ether complex to phenyltrimethoxysilane is (0.8-1.2):1; The total mass fraction of the boron trifluoride ether complex and phenyltrimethoxysilane in the modified solution is 5-8wt.%; The solid-liquid mass ratio of the silicon carbide / molybdenum disulfide composite material to the modified solution is 1:(15-25).

6. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 1, characterized in that: The preparation method of the composite modified metal organic supramolecular cage is as follows: S21: dissolving trimesic acid and zinc nitrate hexahydrate in a mixed solvent of N,N-dimethylformamide and deionized water, performing a solvothermal reaction, filtering, and washing to obtain a metal organic supramolecular cage; S22: calcining melamine to obtain carbon nitride, adding the carbon nitride to concentrated nitric acid for reflux reaction, filtering, washing, and drying to obtain modified carbon nitride, dispersing the modified carbon nitride and the metal organic supramolecular cage in N,N-dimethylformamide, mixing them evenly, and then performing a solvothermal reaction, filtering, washing, and drying to obtain the carbon nitride modified metal organic supramolecular cage; S23: Dispersing the carbon nitride modified metal organic supramolecular cage in anhydrous toluene, adding trifluoropropyltriethoxysilane, reflux reaction, centrifuging, washing, drying to obtain a pretreated product, and vacuum curing to obtain a composite modified metal organic supramolecular cage.

7. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 6, characterized in that: In S21: The molar ratio of trimesic acid to zinc nitrate hexahydrate is 1:(1-2); The volume ratio of N,N-dimethylformamide to deionized water in the mixed solvent is (4-5):1; The total concentration of trimesic acid and zinc nitrate hexahydrate in the mixed solvent is 0.05-0.1M; In S22: The mass ratio of the modified carbon nitride to the metal organic supramolecular cage is (0.8-1.2):1; In S23: The feeding amount of the trifluoropropyltriethoxysilane accounts for 4-6% of the mass of the carbon nitride modified metal organic supramolecular cage.

8. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 1, characterized in that: The preparation method of the composite modified lanthanum-modified carbon nanotubes is: S31: stirring and modifying carbon nanotubes in a modified acid solution to obtain modified carbon nanotubes, dispersing the modified carbon nanotubes in a lanthanum nitrate solution, adding sodium hydroxide to adjust the pH to obtain a reaction solution B, heat-treating under an argon atmosphere, filtering, washing, and drying to obtain lanthanum-modified carbon nanotubes; S32: ultrasonically exfoliating hexagonal boron nitride in N-methylpyrrolidone, collecting the supernatant by centrifugation for later use, dispersing lanthanum-modified carbon nanotubes in N-methylpyrrolidone to obtain a first dispersion, mixing with the supernatant for reaction, vacuum filtering, pre-drying, and heat treating to obtain boron nitride / lanthanum-modified carbon nanotubes; S33: dispersing boron nitride / lanthanum modified carbon nanotubes in anhydrous ethanol, adding 3-aminopropyltriethoxysilane and triethylamine, mixing evenly and reacting at a constant temperature, filtering, washing, pre-drying and then curing to obtain composite modified lanthanum modified carbon nanotubes.

9. The method for preparing a high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack according to claim 8, characterized in that: In S31: The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the modified acid solution is (3-4):1; The mass ratio of the lanthanum nitrate to the modified carbon nanotubes is 1:(8-12); In S32: The concentration of hexagonal boron nitride in N-methylpyrrolidone is 0.5-1 mg / mL; The concentration of lanthanum-modified carbon nanotubes in the first dispersion is 1-2 mg / mL; The mass ratio of the first dispersion liquid to the supernatant liquid is (1.2-1.8):1; In S33: The amount of 3-aminopropyltriethoxysilane added is 4-6% of the mass of the boron nitride / lanthanum modified carbon nanotubes; The feeding amount of the triethylamine accounts for 0.5-1% of the mass of the boron nitride / lanthanum modified carbon nanotubes.

10. A high withstand voltage polysilazane-based insulating material for a new energy vehicle power battery pack prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The mass ratios of polysilazane, organic boron-coated silicon carbide / molybdenum disulfide composite material, composite modified metal organic supramolecular cage, composite modified lanthanum-modified carbon nanotube, crosslinker and flame retardant in the high-voltage polysilazane-based insulating material for new energy vehicle power battery pack are: (80-85):(30-40):(35-45):(25-35):(4-5):(3-4).

Citation Information

Patent Citations

  • Carbon nitride membrane composite material modified on the basis of black phosphorus / MOF (metallic organic frame), and preparation method and application thereof in waste gas processing

    CN108745404A

  • Non-covalent modified boron nitride / epoxy resin heat-conducting insulating composite material and preparation method thereof

    CN115926379A

  • Wear-resistant carbon brush material and preparation method thereof

    CN116505341A

  • High-temperature ablation resistant coating material and preparation method thereof

    CN119220117A

  • Lanthanum-iron-loaded carbon nanotube film for environmental restoration, preparation and application thereof

    US20230125135A1

Cited By

  • Regulation and control process for precipitated phase distribution of regenerated 6XXX series aluminum alloy based on electromagnetic-ultrasonic composite field

    CN120967259A